Digitalisasi Layanan Pengaduan Masyarakat Di Desa Mentoro - Fitri Umardiyah; Moch. Helmi Hendrawan; Shevi Rohimatunnisa; Syafira Nur Fadilla; Muhammad Farid Nasrulloh; Ino Angga Putra; Yuyun Bahtiar (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Villages have a very strategic role in providing services to the public. One important service is the handling of public complaints. In Mentoro Village, the complaint system is still conventional, so that reports from the community are not neatly documented, which risks hindering follow-up and slowing down the response from village officials. The community service team implemented a program with the aim of providing an effective, efficient, and transparent means of conveying the aspirations, complaints, and suggestions of the community to the village government. The community service program was designed to provide solutions through the provision of easily accessible digital-based complaint facilities, such as Google Forms and QR codes, as well as socialization of their use. The activities were carried out in three stages, namely socialization, demonstration, and assistance. Through the implementation of a complaint system based on Google Forms and QR codes, the community now has easier, faster, and more practical access to convey their aspirations, complaints, and suggestions to the village government. This system also helps village officials in documenting reports neatly, systematically, and transparently so that follow-up can be carried out more effectively